Acemannan Induced Bone Regeneration in Lateral Sinus Augmentation Based on Cone Beam Computed Tomographic and Histopathological Evaluation - Hai Anh Trinh; Van Viet Dam; Wijit Banlunara; Polkit Sangvanich; Pasutha Thunyakitpisal (Case Reports in Dentistry)
Acemannan, the major polysaccharide extracted from Aloe vera, is biomaterial that has demonstrated osteoinductive effects in vitro and in vivo. However, the effect of acemannan sponges on bone formation in open-type sinus augmentation has not evaluated. Here, we report a case study using radiographic and histological analyses to investigate the effect of acemannan on bone formation after lateral sinus lift surgery. The case was a 57-year-old female patient with an atrophic left posterior maxilla who underwent lateral sinus lift using an acemannan sponge using the two-stage procedure. In the first stage, an acemannan sponge was inserted through the bony window and placed between the antral floor and the elevated sinus membrane. Cone beam computed tomography (CBCT) images were taken immediately as baseline and 6-month postoperation for evaluation. A bone core specimen was also obtained for histological examination at the time of implant placement. The histological results revealed new bone formation, and the CBCT images demonstrated increased alveolar bone height at 6-month postoperation. Our findings suggest that an acemannan sponge could be a biomaterial for inducing bone formation in sinus lift surgery.